Politik Uang; di Balik Potensi dalam Strategi Kampanye dan Efektivitas Mobilisasi Pemilih dalam Pemilihan Umum Serentak - Adityawan, Riandhika (Journal of Comprehensive Science, 2025)
This study analyzes the phenomenon of money politics in the context of elections in Indonesia. Money politics refers to the practice of providing material incentives, either in the form of money or goods, to voters with the aim of influencing their political preferences. This phenomenon frequently occurs at various stages of the electoral process, from the campaign period to election day. The purpose of this study is to understand the causal factors, implementation mechanisms, and its impact on the quality of democracy and electoral integrity. Using a qualitative approach, data were obtained through literature review, interviews with political experts, and analysis of relevant regulations. The results show that money politics is driven by weak law enforcement, low public political awareness, and a deeply rooted transactional political culture. Its impacts include the delegitimization of election results, the strengthening of political oligarchy, and the degradation of the quality of elected leadership. This study recommends strengthening regulations, increasing political literacy, and stricter law enforcement in Indonesia as strategic steps to minimize the practice of money politics in elections.